Strategy Analysis of Disaster Mitigation for Disability-Friendly (Case Study on Application DIFGANDES by Difagana) - Hindra, Firdaus; Kharismatul Ula, Elok; Hendayana, Yayan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
One of the effects of climate change is an increase in natural disasters, such as floods and droughts. Therefore, there is disaster mitigation to reduce disaster risk. Analysis of disaster mitigation strategies implemented by Difagana through the disability-friendly DIFGANDES application. This research uses a qualitative approach with a type of descriptive research. Data collection is done with interviews as well as secondary data collection. Test validity using time triangulation, technique. An interview with the head of Difagana, Doddy Kaliri, and an observation of the DIFGANDES application.The DIFGANDES application has a variety of disaster mitigation education features that are disability-friendly. For a deaf friend to read the information briefly, equipped with a picture of the pergamon. There are speakers to inform disabled, mentally ill, and elderly people. For mentally disabled people, it is also easy to read brief information. Weather information around the location is also updated. Introducing the DIFGANDES application to the public, especially the disabled, so that they can obtain hate mitigation information, given the increasingly extreme climate change. This research has not reached the wider public using the application as a result of minimizing the cooperation of disaster rescue villages as well as the cost of treatment or development of a considerable number of applications. The catastrophe caused by climate change is highly risky in many respects, so this research into disability-friendly applications is a novelty in reviewing its mitigation strategies.